2004
DOI: 10.1074/jbc.m407477200
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-responsiveness to Stimulation of Human Immunodeficiency Virus-infected CD4+ T Cells Requires Nef and Tat Virus Gene Products and Results from Higher NFAT, NF-κB, and AP-1 Induction

Abstract: ؉ T lymphocytes. Considering that the HIV-1 life cycle is tightly regulated by the T cell signaling machinery, the priming for activation of a major viral reservoir represents a means by which this retrovirus can create an ideal cellular microenvironment for its propagation and maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 86 publications
7
89
2
Order By: Relevance
“…Tat is essential for replication of the viral genome, and it has been proposed that Tat is an important factor in HIV-induced pathogenesis of AIDS (2). Exogenous Tat has a variety of effects on cellular processes in uninfected cells, including increased binding of nuclear factor kappa B (NF-B) to DNA, increased production of cytokines, increased expression of cytokine receptors, and modulation of cell survival and proliferation (2,19,31,34,42). Furthermore, studies have demonstrated that Tat increases apoptosis in a variety of cell types, including cell types not directly infected by HIV-1 (4,42).…”
mentioning
confidence: 99%
“…Tat is essential for replication of the viral genome, and it has been proposed that Tat is an important factor in HIV-induced pathogenesis of AIDS (2). Exogenous Tat has a variety of effects on cellular processes in uninfected cells, including increased binding of nuclear factor kappa B (NF-B) to DNA, increased production of cytokines, increased expression of cytokine receptors, and modulation of cell survival and proliferation (2,19,31,34,42). Furthermore, studies have demonstrated that Tat increases apoptosis in a variety of cell types, including cell types not directly infected by HIV-1 (4,42).…”
mentioning
confidence: 99%
“…In addition, Nef affects the basal states of T cell activation and the responsiveness of T lymphocytes to TCR signaling (24)(25)(26)(27) with the majority of studies that addressed effects of Nef on distal responses to exogenous TCR stimulation by mitogens or anti-TCR Abs reporting a moderate enhancement by HIV-1 Nef (16,(28)(29)(30)(31)(32)(33)(34). In contrast, HIV-1 Nef severely impairs the formation and organization of IS structures between Nef-expressing T lymphocytes and APCs by reducing the frequency of IS formation, blocking Factin polarization at cell-cell contacts, and inducing mislocalization of the TCR itself as well as its effector kinase Lck (28,(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…These effector functions probably reflect the ability of Nef to serve as a protein-interaction adaptor that modulates cellular vesicle transport and signal transduction machineries (5,6). In CD4 ϩ T-lymphocytes, one of the major HIV-1 target cell populations in vivo, Nef lowers the threshold of TCR activation possibly to induce an intermediate activation state that is permissive for HIV-1 replication (7)(8)(9)(10)(11)(12). Several protein assemblies, including the association with the Nef-associated kinase complex, the guanine exchange factors Vav and DOCK2-ELMO1, and the TCR chain, are involved in the modulation of TCR signaling by Nef (13)(14)(15)(16).…”
mentioning
confidence: 99%